2017
DOI: 10.1053/j.ajkd.2016.09.018
|View full text |Cite
|
Sign up to set email alerts
|

CKD and Risk for Hospitalization With Infection: The Atherosclerosis Risk in Communities (ARIC) Study

Abstract: Background Individuals on dialysis have a high risk of infection, but risk of infection in earlier stages of chronic kidney disease (CKD) has not been comprehensively described. Study Design Observational cohort study. Setting & Participants 9,697 participants (aged 53–75 years) in the Atherosclerosis Risk in Communities (ARIC) Study. The participants were followed up from 1996–1998 through 2011. Predictors Estimated glomerular filtration rate (eGFR) and urinary albumin-creatinine ratio (ACR) Outcomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
83
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 114 publications
(91 citation statements)
references
References 34 publications
4
83
3
1
Order By: Relevance
“…The most common cause of death related to suboptimal initiation was found to be infection in the present study; and pneumonia was the leading cause of infectious death among the patients who commenced haemodialysis in a suboptimal manner. In previous studies, the higher mortality and morbidity rates from pneumonia were stated to be well known among incident dialysis patients, and CKD patients from an early stage . In the present study, the patients who died from pneumonia had experienced a longer length of stay and a higher frequency of previous hospitalizations compared to the patients who did not.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…The most common cause of death related to suboptimal initiation was found to be infection in the present study; and pneumonia was the leading cause of infectious death among the patients who commenced haemodialysis in a suboptimal manner. In previous studies, the higher mortality and morbidity rates from pneumonia were stated to be well known among incident dialysis patients, and CKD patients from an early stage . In the present study, the patients who died from pneumonia had experienced a longer length of stay and a higher frequency of previous hospitalizations compared to the patients who did not.…”
Section: Discussionsupporting
confidence: 55%
“…In previous studies, the higher mortality and morbidity rates from pneumonia were stated to be well known among incident dialysis patients, 22 and CKD patients from an early stage. 23 In the present study, the patients who died from pneumonia had experienced a longer length of stay and a higher frequency of previous hospitalizations compared to the patients who did not. Additionally, ADL among patients complicated with pneumonia had remarkably declined, and half of them were already bed-ridden on admission.…”
Section: Discussionmentioning
confidence: 44%
“…Previous studies also reported an increased risk of infection-related death associated with reduced eGFR (Table 1) [8, 15, 16]. However, we should interpret those results carefully since definitions of infection-related death varied across studies.…”
Section: Incidence Of Infectious Disease Associated With Ckdmentioning
confidence: 68%
“…Although age-related immunosenescence may be associated with infection-related mortality, it is also associated with diseases such as diabetes mellitus and chronic kidney disease (22,23). Moreover, there may be a difference between biological age and chronological age.…”
Section: Accepted Manuscript Discussionmentioning
confidence: 99%